Cytokeratin 17, Cytokeratin 19 and BerEP4 expression in basal cell carcinoma and adjacent epithelial structures of the skin - Bartoš, Vladimír (Journal of Pakistan Association of Dermatologists, 2021)
Background Cytokeratin (CK) gene expression in the skin reflects the type of epithelium, the differentiation state of epithelial cells and is subjected to striking modulation upon various challenges including carcinogenesis. Â Objective The aim of the study was to evaluate an immunohistochemical expression status of CK17, CK19 and epithelial cell adhesion molecule EpCAM (BerEP4) in basal cell carcinoma (BCC) and adjacent epithelial structures of the skin. Â Material and Methods Biopsy samples from 20 cases of BCC were investigated. All were stained for CK17 (clone E3), CK19 (clone RCK108) and EpCAM (clone BerEP4) by immunohisto-chemistry. Â Results In normal skin, all three markers were constantly positive in the hair follicle components. TheyÂ were typically negative in the interfollicular epidermis, but the epidermis overlying the tumor and at the edges of tumor mass expressed CK17 in the vast majority of cases. In BCC tissue, the CK17, CK19 and BerEP4 were positive in 100% (20/20), 40% (8/20), and 100% (20/20) of the cases. Â Conclusion BCC constantly express CK17 and BerEP4 and is variably positive for CK19. Since all three markers are strongly positive in the hair follicle but not in the interfollicular epidermis, the staining pattern of CK17, CK19 and BerEP4 in BCC may provide an evidence to the suggestion that the tumor differentiation is toward follicular germinative epithelium. Â